Bumblebees (Bombus terrestris) forage on plants treated with glyphosate-based herbicides despite potential behavioral consequences - Kaakinen, Kimmo; Ramula, Satu; Fuchs, Benjamin; Blande, James D.; Vaajamo, Eva-Maria; Helander, Marjo (Elsevier BV, 2026)
Pesticides are a recognized cause of global insect pollinator decline. Herbicides, which inhibit the growth of weeds, may pose ecotoxicological risks to pollinators. Foraging insect pollinators can encounter herbicides orally when visiting contaminated flowers between the time of application and the plant's death. However, the effects of pesticides on pollinator foraging behavior remain inconsistent. We studied whether buff-tailed bumblebees (Bombus terrestris) visited plants exposed to glyphosate-based herbicides (GBH) when non-contaminated plants were available. Additionally, we examined whether oral exposure to GBH and the presence of an invasive plant (Lupinus polyphyllus) influenced bumblebee foraging behavior. Our findings revealed that bumblebees visited recently GBH-treated plants in both field and flight cage experiments. Furthermore, bumblebees did not discriminate between GBH-treated and uncontaminated plants when the choice was based solely on the plant’s emitted volatile compounds, which changed slightly after exposure. Oral GBH treatment reduced the foraging activity of bumblebees; a higher proportion of exposed bumblebees compared to control bees did not visit any plants. Nevertheless, in the presence of the plant invader, control bees visited fewer plants than GBH-exposed bees. Our results indicate that bumblebees can be exposed to GBH by foraging on recently treated plants, which may have consequences for their foraging behavior, necessitating careful consideration when using GBH products.